2019
DOI: 10.1186/s13068-019-1409-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of non-conserved residues essential for improving the hydrocarbon-producing activity of cyanobacterial aldehyde-deformylating oxygenase

Abstract: Background Cyanobacteria produce hydrocarbons corresponding to diesel fuels by means of aldehyde-deformylating oxygenase (ADO). ADO catalyzes a difficult and unusual reaction in the conversion of aldehydes to hydrocarbons and has been widely used for biofuel production in metabolic engineering; however, its activity is low. A comparison of the amino acid sequences of highly active and less active ADOs will elucidate non-conserved residues that are essential for improving the hydrocarbon-producing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 76 publications
(126 reference statements)
2
21
0
Order By: Relevance
“…Our modelling results suggest that the elimination of the C-terminal sequence has a negative effect on the substrate binding in all three candidates ( Supplementary Fig. 4), which is consistent with the notion that residues far from the active site and the substrate binding site still contribute to the enzyme activity of AD [15].…”
Section: Effects Of Ad Degron Engineering On Alkane Productionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our modelling results suggest that the elimination of the C-terminal sequence has a negative effect on the substrate binding in all three candidates ( Supplementary Fig. 4), which is consistent with the notion that residues far from the active site and the substrate binding site still contribute to the enzyme activity of AD [15].…”
Section: Effects Of Ad Degron Engineering On Alkane Productionsupporting
confidence: 87%
“…ADs are small soluble proteins, which allows them to be studied in vitro more readily, leading to their wider use in metabolic engineering [11,15,[23][24][25][26]. Although new bacterial AD is constantly being characterized and engineered for alkane production [11,22,23,27,28], our experiments showed that protein accumulation of bacterial ADs is limited in vivo.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Among these, both plant and insect ADs are membrane proteins, complicating their characterization in vitro. In contrast, bacterial ADs are small soluble proteins, which allows them to be studied in vitro more readily, leading to their wider use in metabolic engineering [11,15,[23][24][25][26]. Although new bacterial AD is constantly being characterized and engineered for alkane production [11,22,23,27,28], our experiments showed that protein accumulation of bacterial ADs is limited in vivo.…”
Section: Introductionmentioning
confidence: 82%
“…To our knowledge, the highest reported value for long chain alkane production is 2.54 g/L (C13-C17) in engineered Escherichia coli [7], but this is still insufficient for industrial scale-up. It has been reported that the low efficiency of AD is the bottleneck of alkane production [4,14,15], which warrants further investigation into how ADs behave in vivo.…”
Section: Introductionmentioning
confidence: 99%